The Sequence and Three-Dimensional Structure Characterization of Snake Venom Phospholipases B - Ullah, Anwar; Masood, Rehana (Frontiers in Molecular Biosciences, 2020)
Snake venom phospholipases B (SVPLBs) are the least studied enzymes. They constitute about 1% of Bothrops crude venoms, however, in other snake venoms, it is present in less than 1%. These enzymes are considered the most potent hemolytic agent in the venom. Currently, no structural information is available about these enzymes from snake venom. To better understand its three-dimensional structure and mechanisms of envenomation, the current work describes the first model-based structure report of this enzyme from Bothrops moojeni venom named as B. moojeni phospholipase B (PLB_Bm). The structure model of PLB_Bm was generated using model building software like I-TESSER, MODELLER 9v19, and Swiss-Model. The build PLB_Bm model was validated using validation tools (PROCHECK, ERRAT, and Verif3D). The analysis of the PLB_Bm modeled structure indicates that it contains 491 amino acid residues that form a well-defined four-layer αββα sandwich core and has a typical fold of the N-terminal nucleophile aminohydrolase (Ntn-hydrolase). The overall structure of PLB_Bm contains 18 β-strands and 17 α-helices with many connecting loops. The structure divides into two chains (A and B) after maturation. The A chain is smaller and contains 207 amino acid residues, whereas the B chain is larger and contains 266 amino acid residues. The sequence and structural comparison among homologous snake venom, bacterial, and mammals PLBs indicate that differences in the length and sequence composition may confer variable substrate specificity to these enzymes. Moreover, the surface charge distribution, average volume, and depth of the active site cavity also vary in these enzymes. The present work will provide more information about the structure–function relationship and mechanism of action of these enzymes in snakebite envenomation.